Towards a theory of Deference in South Africa; Trans-Atlantic Lessons - Kenny, John (Department of Public Law, 2014)
This paper will offer a 'snapshot' designed to demonstrate the analytical poverty of a bare constitutional approach shorn of intellectually comprehensible criteria. It will be argued that this approach fails to offer a coherent corpus of law, oscillating alternatively between formalistic bows to deference and judicial interventions of extraordinary ambition. The thrust of the analysis with the normative model will not be to quibble with the impact of the Constitution, but rather to argue for a return to a conceptual analysis where the doctrine of deference is not determined haphazardly by reference to the Court's solicitude for a particular constitutional right. It will be briefly argued that the courts in South Africa have been waylaid by the interpretative millstone of determining whether a contested decision is "administrative action", often encapsulating their entire deference analysis within a perfunctory nod to separation of powers principles. It will be argued that the South African judiciary has refused to grasp the nettle of an overtly conceptual justification for judicial review. Their current approach, of stressing the requirement of 'reasonablness', it will be argued begs rather than answers the demand for substantive criteria that subsist beyond the particular circumstances of each case. In lieu of such conceptual poverty it will be argued that there are important lessons to be gleaned from the deference jurisprudence of the United States Supreme Court. Revolving around the twin pivots of Chevron USA Inc v Natural Resources Defense Council and Skidmore v Swift Co., the justifications for deference underpinning this dual standard will be examined. In order to advance the debate from the unhelpful totems of 'rationality' and 'reasonablness' review, the American experience with the concrete justifications of legislative intent and agency expertise will be sketched. The South African material will be prevented through the prism of Jacque De Ville's theory. It will be argued that there is no warrant for the conceptual excess's of his programme. Rather the few post-1994 cases that have dealt expressly with deference will be adverted to, and an attempt made to elicit a skeletal model from the rather sparse dicta The paper will conclude with a modest proposal for a process rationale for deference, broadly based on a Skidmore-hard look paradigm to reconcile the two emerging streams of the jurisprudence. It will be argued that it promises the genesis of a deference jurisprudence which offers the prospect of incorporating agency expertise into the judicial calculus yet preserves the hallowed admonition that those "who are limited by the law ought not to be entrusted with the power to define the limitation".